Level Of Awareness Of Energy Saving Measures Of Electricity Users At Universities In Kenya (International Journal of Engineering and Computer Science, 2018)
Energy is a crucial factor for economic competitiveness and employment and hence a large amount of it is required in countries with faster economic growth. Higher institutions of learning such as universities spent a lot of money on energy bills because of the nature of their daily activities. This study sought to determine the level of awareness of saving measures of electricity users at universities in Kenya. A survey research design was used in this study. Questionnaires, interview schedules and personal observation methods were employed in collection of data and the collected data was analysed using descriptive statistics and were done with the help of the statistical package for the social sciences (SPSS) computer program. The findings revealed that End-users had not been trained on electric energy saving measures and that there was no university policy on energy saving that could guide the users.  The study therefore concluded that the level of awareness of energy saving measures of electricity users at the universities in Kenya was too low and that there was an urgent need for universities to take action to save wastage of electric energy in the institutions of higher learning.